Effect of rare-earth (Er and Gd) substitution on the magnetic and multiferroic properties of DyFe0.5Cr0.5O3. (2nd September 2016) - Sharma, Mohit K; Basu, Tathamay; Mukherjee, K; Sampathkumaran, E V
Abstract: We report the results of our investigations on the influence of partial substitution of Er and Gd for Dy on the magnetic and magnetoelectric properties of DyFe0.5 Cr0.5 O3, which is known to be a multiferroic system. Magnetic susceptibility and heat capacity data, apart from confirming the occurrence of magnetic transitions at ~121 and 13 K in DyFe0.5 Cr0.5 O3, bring out that the lower transition temperature only is suppressed by rare-earth substitution. Multiferroic behavior is found to persist in Dy0.4 Ln0.6 Fe0.5 Cr0.5 O3 (Ln  =  Er and Gd). There is an evidence for magnetoelectric coupling in all these materials with qualitative differences in its behavior as the temperature is changed across these two transitions. Remnant electric polarization is observed for all the compounds. The most notable observation is that electric polarization is seen to get enhanced as a result of rare-earth substitution with respect to that in DyFe0.5 Cr0.5 O3 . Interestingly, a similar trend is seen in the magnetocaloric effect, consistent with the existence of magnetoelectric coupling. The results thus provide evidence for the tuning of magnetoelectric coupling by rare-earth substitution in this family of oxides.